Morphometric and Growth Pattern Analysis of Corpus Callosum in Paediatric Population on Magnetic Resonance Imaging: A Retrospective Observational Study - Sweta Swaika; Harshit Koshta; Apurva Shukla (Journal of Clinical and Diagnostic Research)
Introduction: There is development and myelination of axons within the Corpus Callosum (CC) in children and early adulthood, causing modifications in its various dimensions. Previous studies have reported age-wise and/or sex-related variations in morphological measurements of CC in different population groups. Aim: To evaluate the age and sex-related disparity in morphometric parameters of CC and derive growth curve of CC in children in the central Indian population. Materials and Methods: A retrospective observational study was done in Radiology Department, Gajra Raja Medical College, Gwalior, Madhya Pradesh, India, from January 2020 to June 2023. Study was conducted in 141 children with ≤15 years of age. CC was manually evaluated on mid-sagittal T2-weighted images for following measurements: Anteroposterior Length (APL), Total Length (TL), maximum Genu Thickness (GT), mid-Body Thickness (BT), maximum Splenium Thickness (ST), Maximum body Thickness (MT) and Height (HT). The Anteroposterior length of Brain (APB) was measured, and ratio between APL and APB was calculated (APL/APB). All the subjects were divided according to five age groups: group 1 (≤1 year), group 2 (>1-≤3 years), group 3 (>3-≤5 years), group 4 (>5-≤10 years) and group 5 (>10-≤15 years). Data analysis was performed using International Business Machines (IBM) Statistical Package for the Social Sciences (SPSS) software version 29.0, using student’s t-test, Chi-square test, Spearman’s correlation and linear regression. Results: The mean±Standard Deviation (SD) age was 6.5±4.9 years. The study included 83 (58.9%) males and 58 (41.1%) females. The study revealed periods of major increase between birth to three years and between 5-10 years. The CC growth in children and adolescents had a non linear course with periods of peak and plateau phases in between. Linear regression showed a significant correlation between APB and age (independent parameter) and the CC dimensions (dependent parameter). There was no considerable difference in these dimensions between the sexes. Conclusion: In the current study, there were age-wise variations in CC dimensions in paediatric population (≤15 years) without any sex-related differences. The present study values helps to understand the variations in CC with age-wise brain development.